Integer coefficients partial response signaling in OFDM system - Syed Yusof, Sharifah Kamilah; Fisal, Norsheila; Muladi (2006)
Orthogonal Frequency Division Multiplexing (OFDM) is a successful technique in wireless communication system. However, frequency offset in OFDM system leads to loss of orthogonality among subcarriers, which resulted in intercarrier interference (ICI) to occur. To improve bandwidth efficiency performance in ICI self-cancellation schemes, frequency domain partial response signaling (PRS) has been studied. In this paper, the integer polynomial partial response coefficients are exploited to enhance carrier-to-interference power ratio (CIR) in OFDM system. The CIR is enhanced by about 3.8 dB up to 4.7 dB when the length of PRS polynomial, K is 2, 3, and 4 respectively.